'Heepa' (hail) Òrìşà: the òrìsà factor in the birth of Yoruba identity - Ojo, Olatunji (Journal of Religion in Africa, 2009)
The popularization of Christianity and Islam among Yoruba-speaking slaves in the diaspora is widely seen as the root of Yoruba ethnic consciousness. Returning ex-slaves, Christians, and British colonialists starting in the 1830s, in a form of reversing sail, propagated this identity in the homeland among those who did not cross the Atlantic. This essay suggests that the focus on world religions off ers only a partial explanation of the evolution of this consciousness in the homeland. The essay identifies what role orisa worship practice and its conductors played in the birth of Yoruba ethnicity. It argues that as in the diaspora, nineteenth-century homeland Yoruba witnessed substantial population mixture, urbanism and interethnic marriage in ways that transformed orisa from local to regional symbols. Based on the web of links created among the Yoruba, the prescriptions of diasporic Yoruba and their supporters could be understood and accepted by the majority of those left behind because they drew upon existing commonly shared beliefs. Nonetheless, these conditions were not sufficient for the birth of a nation. The nation needs its advocates. Returning Yoruba ex-slaves, aided by the Christian church and European colonialists, reduced Yoruba language into writing and made the text the symbol through which others were persuaded and trained to accept the Yoruba nation. In the diaspora and later the homeland, common language distinguished the Yoruba from their neighbors, especially the multitude of ethnicities that merged into the Nigerian state.
free
Keywords: Christianity and African religions; Group identity; Language question in the mission field; Orisha religion; Repatriation; Slave trade; Symbolism; Yoruba (African people)